Field Simulation of Dipole Antennas for Interstitial Microwave Hyperthermia. - Erb, J.; Engelbrecht, Rainer; Schaller, Gerhard (IEEE Transactions on Microwave Theory and Techniques, 1996)
The electromagnetic field of dipole antennas for interstitial microwave hyperthermia is investigated using a finite integration algorithm program. The numerical method is applied to conventional, clinically used applicators and is also used for the improvement and optimization of sophisticated applicators, e.g., in a triaxial technique. Simulations of the frequency dependent impedance match, the E-fleld and the specific absorption rate (SAR) distribution of different applicators immersed in a muscle phantom are presented and compared with measurements. Moreover, results for arrays of two and four applicators are given. The field simulation allows one to study the effects at the various discontinuities of the applicator-catheter-tissue system and gives a better understanding of known phenomena. © 1996 IEEE.
UnivIS-Import:2015-03-05:Pub.1996.tech.IE.LEH.fields